The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1159/000523993
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing COVID-19 Vaccine Hesitancy among University Students in UAE: A Cross-Sectional Study

Abstract: <b><i>Introduction:</i></b> While vaccines may be a key measure in overcoming the pandemic, their hesitancy among the population may impede the ongoing efforts of governments and health authorities in a country. Universities are considered the hubs of the transition of individuals to young adults, understanding the hesitancy of this population stratum and addressing apprehensions that may exist is of utmost importance. This study aims to explore the attitude and hesitancy of students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In a study that explored the attitude and hesitancy of students in UAE universities toward the Covid-19 vaccines, majority of participants were female respondents (76.6%) and the average age of respondents was 21 y, similar to our study (73.5% and 20 y respectively). But vaccine coverage is lower than (67%) our study (84%) [21]. 61.89% of medical students were not vaccinated for Covid-19 in a Caribbean medical school [22], Where as it was 61.9% in another study [23].…”
Section: Resultscontrasting
confidence: 64%
“…In a study that explored the attitude and hesitancy of students in UAE universities toward the Covid-19 vaccines, majority of participants were female respondents (76.6%) and the average age of respondents was 21 y, similar to our study (73.5% and 20 y respectively). But vaccine coverage is lower than (67%) our study (84%) [21]. 61.89% of medical students were not vaccinated for Covid-19 in a Caribbean medical school [22], Where as it was 61.9% in another study [23].…”
Section: Resultscontrasting
confidence: 64%
“…Of the 52 included studies, seven [ 30 , 50 , 66 , 69 , 73 , 74 , 76 ] did not report formal VH/VA rates. However, as these studies reported factors associated with intentions to vaccinate, the decision was made to include them for review.…”
Section: Resultsmentioning
confidence: 99%
“…Higher rates of VH were observed in African and Middle Eastern countries, with medical students reporting higher rates of belief in conspiracy theories about COVID-19 vaccines [ 34 , 48 , 50 , 63 ]. There was also greater mistrust in government and public health experts’ COVID-19 vaccine information and a higher level of trust placed in the opinions of family members, relatives, and social media when making vaccination decisions within VH populations [ 27 , 36 , 37 , 43 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%